(untitled) (Journal of Media, Journalism & Mass Communication, 2025)
The digital revolution has transformed how we talk to each other during emergencies. Now it’s easier for everyone to share information and data, which makes it tougher to check that information is correct in emergencies. The purpose of this study is to learn more about the challenges that arise and how to check the authenticity of information and the trustworthiness of sources in user-generated crisis content by looking at how citizen journalism works during natural disasters and man-made emergencies. This research focuses at how different kinds of crises affect credibility indicators, verification processes, and reliability in digital ecosystems. It does this by doing a detailed comparison that uses data from several platforms, interviews with stakeholders, and case studies that last for a long time. The results of this study reveal that emergencies created by individuals make politically and emotionally charged content that needs better ways to check facts and find bias. Natural disasters, on the other hand, frequently lead to more factual, location-specific material with easier ways to check it and better community engagement. The study concludes that the usual approaches of measuring credibility need to be adjusted to fit the needs of each type of crisis. These developments have a big effect on how media literacy is taught, how platforms are designed, how emergency communication strategies are made, and how regulations are made.